Assessment of Fluid Transport Mechanisms in Shale Gas Reservoirs - Testamanti, Maria Nadia (Curtin University, 2018)
The complex interplay between the physical and flow properties of shales was investigated. A methodology was developed to estimate free and bound porosity fractions from NMR-T2 experiments on shales, while a second order flow model was proposed to interpret gas permeability data. Slippage effects appeared to be influenced by characteristic pore lengths, while poroelastic behaviour was linked to compositional data. Potential associations emerged between FFI/BVI, pore sizes, fluid dynamic phenomena, and shale composition.